AI TOOLS IN CURRICULUM DESIGN AND LAN GUAGE TESTING: TRANSFORMING EDUCATI ONAL PRACTICES IN THE DIGITAL AGE - Jakbarova Nasiba Po‘latjonovna (Western European Studies, 2026)
This study examines the integration of artificial intelligence (AI) tools in curriculum design and language testing within educational contexts. As AI technologies rapidly evolve, their application in educational settings presents both opportunities and challenges for language educators and curriculum developers. This article explores current AI implementations, analyzes their effectiveness in curriculum design and assessment practices, and discusses implications for future educational practice. Through a comprehensive review of recent literature and case studies, the research identifies key AI tools, their pedagogical applications, and their impact on learning outcomes. Findings suggest that AI tools significantly enhance curriculum personalization, assessment efficiency, and feedback quality, while also raising important considerations regarding pedagogical integrity, equity, and the evolving role of educators.
Keywords: Artificial Intelligence; Curriculum Design; Language Testing